Upaya Peningkatan Penguasaan Kosa Kata Arab dengan Metode Bernyanyi Kelas VII B MTsN 6 Sleman Yogyakarta - Zumrotul Aslah (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2017)
Vocabulary mastery in a language greatly influences a person's ability to use the language both receptively and productively. Likewise in Arabic, this paper aims to find out the mastery of Arabic vocabulary in class VII B students with the singing method. This type of research is a field research using PTK (Classroom Action Research) design, with a cycle model. Data collection techniques include a pretest, posttest, and observation of students' attitudes toward the learning process. While the data analysis used is qualitative and quantitative descriptive. The results of data analysis show that the learning process with singing methods can improve students' Arabic vocabulary. This is evidenced in the results of observations and the learning process with the singing method, both in pre-cycle, cycle I and cycle II, which is very enjoyable for students. Student activity in classroom learning is memorizing Arabic vocabulary (mufradat) on average 28.2 words (49.47%) on pre-cycle, increasing to 36 words (63.16%) in cycle I and increased significantly to 48, 8 words (85.61%) in cycle II.